A comparative review of how the policy and procedures to assess research impact evolved in Australia and the UK. Issue 2 (11th January 2018) - Williams, Kate; Grant, Jonathan
Abstract: This article offers a systematic review of the evolution of research impact assessment in Australia and the UK. We consider its inception and detail the development of relevant policy and procedures in each country. The article sets out the results of a comparative analysis of public policy documents, newspaper commentary, and academic literature in both countries. We examined the differences and commonalities between the two nations, revealing evaluation criteria and uncovering justifications for the adoption of impact assessment. The article highlights the convergence and divergence of the two countries' policy and procedures, as well as the political and bureaucratic contexts that have shaped their design and implementation. The article shows that the synergistic, intermittent, and iterative development of relevant policy and procedures in the two nations has been mutually beneficial for the evolution of retrospective impact assessment.